Knowledge and Awareness among Registered Nurses in the Prevention of Venous Thromboembolism (VTE) for High-Risk Antenatal and Postnatal Mothers - Yee , Bit-Lian; Janet Sano; Rosnida Abu Bakar (Lincoln University College, Asia Pacific Higher Learning Sdn Bhd, 2022)
Background: There is an increment in the incidence of venous thromboembolism (VTE) among the Asian population. This study is conducted to investigate the level of knowledge and awareness of the nurses regarding VTE. Methods: A cross-sectional descriptive study was conducted with 170 respondents who fulfilled the inclusion criteria. The respondents’ knowledge and awareness were assessed by using an individual VTE self-efficacy items with 5-point Likert scale. Results: The finding shows no significant relationship between age, education level, nurse grade, experience, attend CNE with the knowledge level. There is significant relationship between attend CNE and level of awareness. Conclusion: In this study, it was discovered that the level of knowledge and awareness among nurses in the government hospital were at good level. However, more studies should be conducted to compare among the hospitals. This will capture a clear picture regarding nurses’ knowledge and awareness regarding VTE management.